AB0389 Methotrexate Treatment for Rheumatoid Arthritis in Poland: Retrospective Analysis of Patients in Routine Clinical Practice. (15th July 2016) - Świerkot, J.; Batko, B.; Stajszczyk, M.; Jedrzejewski, M.; Wiland, P.
Abstract : Background: Methotrexate (MTX) is a folic acid antagonist which has both an antiproliferative and an anti-inflammatory action. It is the most commonly prescribed DMARD (disease-modifying antirheumatic drug) and is considered the "anchor drug" in rheumatoid arthritis (RA). Objectives: Our study reviews RA treatment with MTX in Poland. Methods: Presented study was based on a retrospective analysis of a cohort of 1957 patients with RA in routine clinical practice. The study was conducted among 100 rheumatologists from different centers that have been selected to reflect the structure of the treatment of RA in Poland. Each physician received 20 questionnaires that were filled on the nearest visit of consecutive 20 patients with RA. Data was collected using pre-defined questionnaire. Results: MTX was taken by 91% of patients and 80% of them continued the treatment both as monotherapy (65%) or concomitantly with other DMARDs. In general, the therapy was initiated within 6 months after diagnosis in 60% of cases. However, MTX was introduced at the very beginning of the treatment for the majority of patients diagnosed after 2009. Methotrexate was given mostly orally, nevertheless in case of 18% of patients it was administered subcutaneously. During MTX treatment dose modifications could be observed in 76% cases and were contingent on different factors. Lack of efficacy was the major reason for increase, while the most common cause of reduction the dose was intolerance of MTX or presence of adverse events, like the most prevalent nausea and vomiting, weakness, increase in activity of liver enzymes and hair loss. Initial dose of MTX was mostly 10 or 15 mg/week. An increase in dosage to 25 mg/week was observed in 36% cases and was continued for 27% of patients. Medium maximum dose that was achieved during treatment was 20.2 mg/week (median 19.3 mg/week). Patients who currently take MTX primarily use a dose of 25 mg/week (27%), 20 mg/week (24%) or 15 mg/week (21%). Treatment interruption was noted in 21% patients predominantly due to intolerance to MTX, however in 13% of cases it was patient's decision. More than half of patients (61%) treated for 3–6 months with MTX achieved remission or low disease activity based on DAS-28. Conclusions: MTX when used according to current recommendations is a effective drug, taking into account the efficacy and adverse effects. To optimize the MTX therapy regular control visits are required Disclosure of Interest: J. Świerkot Grant/research support from: supported by Roche, B. Batko Grant/research support from: supported by Roche, M. Stajszczyk Grant/research support from: supported by Roche, M. Jedrzejewski Grant/research support from: supported by Roche, P. Wiland Grant/research support from: supported by Roche